Cost-Effectiveness Analysis in Health Care Based on the Capability Approach - Gandjour, A. (Das Gesundheitswesen, 2014)
It is well known that Sen’s capability approach and preference utilitarianism have different distributional values. The purpose of this paper is to discuss how Sen’s capability approach might be operationalised for allocation decisions and cost-effectiveness analysis in health care. The paper identifies several requirements for measuring health or well-being in line with the capability approach. Among them is the need for objective assessments of capabilities. This paper also shows that from the perspective of the capability approach a portion of productivity changes are irrelevant for allocation decisions.
Keywords: resource allocation; cost-effectiveness; capabilities; utilitarianism